Structural equation modeling of the impact of mandibular ridge form and denture quality on oral health-related quality of life in complete denture wearers. Issue 3 (July 2019) - Yamaga, Eijiro; Sato, Yusuke; Soeda, Hitomi; Minakuchi, Shunsuke
Abstract: Purpose: To examine the effect of mandibular ridge form and denture quality on oral health-related quality of life (OHRQoL) in complete denture wearers by using structural equation modeling (SEM) analysis of data before and after new complete denture insertion. Methods: Four hundred thirty-two edentulous patients who visited the Dental Hospital of Tokyo Medical and Dental University for new complete dentures were recruited. An intervention study design was conducted, including complete denture fabrication with SEM analysis. Mandibular ridge form, mandibular denture stability, accuracy of jaw relation record, and the Oral Health Impact Profile for edentulous subjects (OHIP-EDENT-J) total score before and after new complete denture insertion were used in the hypothesized model. Results: Two hundred and thirty-seven participants completed the research. SEM analysis demonstrated adequate model fit. Path coefficients of mandibular ridge form to OHIP-EDENT-J before and after insertion, and mandibular denture stability to OHIP-EDENT-J before insertion, were significant. Conclusions: This study demonstrated that mandibular denture stability and mandibular ridge form are important to ensure successful complete denture therapy.